1980
DOI: 10.1128/iai.27.2.597-603.1980
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a flagellar sheath protein of Vibrio cholerae

Abstract: A flagellar sheath protein of Vibrio cholerae CA401 (Inaba) was characterized. Purity of the preparation was indicated by a single band on polyacrylamide gel electrophoresis gels and on Ouchterlony plates prepared with antibody against crude sheath material. The sheath protein was composed of three polypeptides with minimal molecular weights of 61,500, 60,000, and 56,500. The presence of sheath protein on the flagellum as well as on the outer membrane of the cell was demonstrated by ferritin labeling experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…A membrane sheath covers the flagellar core and appears to be contiguous with the outer membrane (114). The proteins associated with the flagellar sheath have been variously reported to be three polypeptides of 56, 60, and 61.5 kDa (179) or two proteins of 38 and 40 kDa (410). Antibodies against the 38-and 40-kDa proteins inhibited motility of V. cholerae, but these proteins did not induce protective immunity against disease in the rabbit (368).…”
Section: Colonization Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A membrane sheath covers the flagellar core and appears to be contiguous with the outer membrane (114). The proteins associated with the flagellar sheath have been variously reported to be three polypeptides of 56, 60, and 61.5 kDa (179) or two proteins of 38 and 40 kDa (410). Antibodies against the 38-and 40-kDa proteins inhibited motility of V. cholerae, but these proteins did not induce protective immunity against disease in the rabbit (368).…”
Section: Colonization Factorsmentioning
confidence: 99%
“…A variety of workers have shown that nonmotile, fully enterotoxinogenic mutants are naturally diminished in virulence (10,149,365,391). In addition to its role in motility, it has also been suggested that the flagellum serves as an adhesin (10,93,179). One relevant issue concerns whether it is the mere presence of a flagellum that is sufficient for colonization or whether it is the actual property of motility that is important.…”
Section: Colonization Factorsmentioning
confidence: 99%
“…Microscopic studies together with immunolabelling analyses revealed that the single-flagellum sheath is a continuation of the cell wall (Glauert, 1968;Fuerst and Perry, 1988;Burygin et al, 2007). Interestingly, Hranitzky et al have reported that although the sheath protein was detected on the flagellum as well as on the outer membrane of the V. cholerae cells, antibody specific for lipopolysaccharide labelled the cell but not the sheathed flagellum (Hranitzky et al, 1980). Therefore, they proposed that the sheath is not a simple extension of the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively studied are polar and peritrichous flagella. Interestingly, the polar flagella are surrounded by sheaths in several bacteria including marine Vibrio species (Furuno et al, 2000;McCarter, 2001), Vibrio cholerae (Hranitzky et al, 1980;Fuerst and Perry, 1988), Bdellovibrio bacteriovorus (Thomashow and Rittenberg, 1985), Pseudomonas stizolobii (Fuerst and Hayward, 1969), Helicobacter pylori (Geis et al, 1993;Luke and Penn, 1995;O'Toole et al, 1995) and Azospirillum brasilense (Burygin et al, 2007). Each sheath encloses one flagellar filament.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation